Implementation of wavelet transform based on switched current circuits - Hu Qinchun (Dianzi Jishu Yingyong, 2018)
In order to meet the engineering application requirement for low-power and real-time signal processing, an implementation of wavelet transform using switched current(SI) technique is presented in this paper. The working principles of wavelet transform, both in time-domain and frequency-domain are discussed. The circuits are composed of analog filter banks whose impulse responses are the first derivative of Gaussian. By adjusting the clock frequency of SI circuits, the wavelet transform in differential scales are able to be performed. The good performance of the proposed method is verified by simulated results.